Crack tip parameters for large scale yielding - Glavardanov, Ivan (Journal of Production Engineering, 1989)
This paper introduces a simple correction for crack tip fields using a quasi-deformation plasticity theory that takes into account nonproportional loading. The analysis is employed to extend fracture mechanics concepts beyond the normal limits of J-integral theory. A straightforward correction for crack tip stresses is derived from the quasi-deformation assumption. This correction suggests that the degree of crack tip triaxiality is related to the relationship between the el-integral and the crack tip opening displacement (CTOD). Predictions of crack tip stress fields agree well with published finite element results.